Feitiços audiovisuais de uma travesti preta: a estética-política (en)cantada dos videoclipes de Linn da Quebrada - Dias, Ed Ney Borges (2021)
Self-defined Black travesti and multimedia artist, Linn da Quebrada produces audiovisual works in the Brazilian contemporary scene that denounce and react to the oppressions of a white heteronormative cystem - cissexist system (VERGUEIRO, 2015). For Linn da Quebrada, her art acts as a spell (feitiço) in the materialization of new ways of thinking / feeling and in creating fissures in the imaginaries of a racist, heterosexist and patriarchal cisgenderness. This research conjures up reflections on the artist's enchanted political-aesthetic and understands her music videos as audiovisual spells (feitiços audiovisuais), active in the promotion of trans and Black life in the Brazilian context. Here the "feitiço" is understood as an insurgent technology of intervention in the social reality activated by Black women (RAMOS, 2020) – or, more broadly, womenhood – to face the plantation of death of colonial disenchantment (SIMAS; RUFINO, 2020). Absolutas (2017), blasFêmea | Mulher (2017), Serei A (2017) e Oração (2019) are the works analyzed, with a methodological perspective thought from the performance-space-time tripod (SOARES, 2012) and an intersectional approach (CRENSHAW, 2002; COLLINS, 2017). With her "feitiços audiovisuais", Linn da Quebrada strengthens Black trans people, queer (or cuir in a Brazilian twist of the English-speaking term), and sexual and gender dissidents in their daily processes of re-existence (AMORIM, 2019) and of healing colonial traumatic wounds (KILOMBA, 2019). The artist's works, then, function as communicative strategies, based on the constitution of bonds, which articulate sounds, images, words and bodies to create collective memories and audiovisual possibilities of Black and travesti life in Brazil. KEYWORDS: Spell; Linn da Quebrada; Queer/cuir; Black trans people; Music video.